Membrane enrichment of genetic markers close to the origin and terminus during the deoxyribonucleic acid replication cycle in Bacillus subtilis. - Beeson, J (1979)
A temperature-sensitive Bacillus subtilis initiation mutant was used to achieve one cycle of synchronized deoxyribonucleic acid (DNA) replication. Markers near the origin of replication and the terminus were assayed for association with the cell membrane at intervals during the DNA replication cycle. DNA near the origin and terminus was found to be enriched in the membrane fraction throughout the DNA replication cycle. The magnitude of membrane enrichment or origin and terminus markers varied coincidentally, possibly as a consequence of incubating the cells at 45 degrees C.